2016
DOI: 10.1111/cfs.12337
|View full text |Cite
|
Sign up to set email alerts
|

Engaging on the ‘front line’: exploring how family support teams construct meaning in their work with young mothers

Abstract: This paper explores the provision of family support services for young mothers within a Sure Start Children's Centre, drawing on data collected within a larger study. It identifies how the family support team attempted to build supportive relationships with young mothers between the ages of 16 and 19 years. The findings presented here draw on narrative interviews (n = 10) and focus group interviews (n = 2) with the family support team that included early years workers, family support workers and their managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Researchers have suggested that formal support services must be non-judgmental and empathetic, enabling mothers to cope with CSA trauma and encouraging them to engage with professionals (Leese, 2016;Letourneau et al, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Researchers have suggested that formal support services must be non-judgmental and empathetic, enabling mothers to cope with CSA trauma and encouraging them to engage with professionals (Leese, 2016;Letourneau et al, 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Both professionals and parents participating in activities in family centres highlight the significance of focusing on families' resources and listening to how they understand their own situation. This approach influences both parents' ability to build trust in professionals and also to position the professionals as able to support families both directly and by connecting them to other services (Bulling, ; Leese, ). From a professional perspective, the centres lower the threshold for interdisciplinary collaboration (Busch et al, ) although the potential for collaboration is not always fulfilled.…”
Section: Introductionmentioning
confidence: 99%